Reconstruction of non-error magnetic hologram data by magnetic assist recording. Issue 1 (December 2017) - Shirakashi, Zen; Goto, Taichi; Takagi, Hiroyuki; Nakamura, Yuichi; Lim, Pang; Uchida, Hironaga; Inoue, Mitsuteru
Abstract Hologram memory is expected to be the next-generation of optical data storage technology. Bismuth-substituted yttrium iron garnet is typically used for rewritable magnetic hologram media. The diffraction efficiency of magnetic holography depends on the Faraday rotation angle, but the experimental diffraction efficiency is not as high as that expected from calculations. This difference could be caused by incomplete magnetization reversal at the recorded region. In this study, we investigated the effects of magnetic assist (MA) recording through numerical simulation and experiment to improve the diffraction efficiency and the resulting reconstructed images. The improvement of diffraction efficiency was more effective in garnet films thinner than the width of a fringe, and a suitable value of the assist magnetic field was identified for the improvement. In addition, MA recording improved the intensity of reconstructed images and broadened the non-error recording conditions to the low energy region. This technique shows promise in improving the reconstructed quality of magnetic hologram data.